Silicon Devices and Process Integration Deep Submicron and Nano-Scale Technologies - El-Kareh, Badih (Springer US : Imprint: Springer, 2009)
Silicon Devices and Process Integration is compiled from industrial and academic lecture notes and reflects years of experience in the development of silicon devices. It is prepared specifically for engineers and scientists in semiconductor research, development and manufacturing. It is also suitable for a one-semester course in electrical engineering and materials science at the upper undergraduate or lower graduate level. The book covers both the theoretical and practical aspects of modern silicon devices and the relationship between their electrical properties and processing conditions. Topics covered include: MOS structure, parameter extraction - Short and narrow-channel effects - CMOS mobility enhancement techniques - High-K gate dielectrics, advanced gate stacks - Low-K dielectrics and Cu interconnects - Analog devices and passive components - CMOS and BiCMOS process integration - DRAM, SRAM and NVM cell structures. The book covers state-of-the-art silicon devices and integrated process technologies. It represents a comprehensive discussion of modern silicon devices, their characteristics, and interactions with process parameters.